University Extension and Education in/for Health: knowledge, prevention and control of syphilis (Research, Society and Development, 2021)
The university extension activities are a form of interaction between the university and the community, and based on it, different health promotion activities can be developed, as the sustainable development of vulnerable communities for example. Syphilis is a sexually transmitted infection that can present asymptomatic or symptomatic forms and has affected countless people around the world. In Brazil, the number of infected people has increased over the years, even with the SUS providing treatment, which is quite worrying due to congenital syphilis. With the growth of infected people in the country, especially in the state of Pernambuco, it is essential to fight syphilis through preventive actions. Teaching and learning strategies such as health education demonstrate the transforming role of university extension for undergraduates and society, aiming to contribute to the academic training of undergraduates through the exchange of knowledge. The activities to raise awareness about syphilis were held in a conversation circle during the Science and Technology Week, CECINE-UFPE/2019, and in the Parasitology course at UFPE. At the end of each exhibition, information leaflets and condoms were also distributed. At first, the students were shy when they saw illustrated panels with syphilitic lesions and condoms on the benches. However, as the interaction progressed, they were amazed by the epidemiology, exposing their doubts and prior knowledge on the subject. With each new action, the extension workers understood more about the social commitment and demonstrated more security. Thus, the project contributes to the academic training of undergraduates, providing the development of educational practices with students, who become agents for disseminating knowledge in the fight and prevention of syphilis in their social spaces.